Bending Effect on the Single Mode Optical Fibers - Thomas, Nejla P. S.; Hasan, Hasan A.; Al Naimee, Kais A. (Iraqi Journal of Laser, 2005)
Bending effects on the transmission of optical signal are investigated on a single mode optical fiber (SMOF) of 10 m length, core radius of 5 μm and optical refractive index difference 0.003. The bending radii (R) were between 0.08 and 0.0015 m. A great decrease in the amplitude is shown for radii below 0.01 m. Sudden break down occurs for radii less than 0.0015 m. Birefringence (B) is difficult to measure for long fibers. Meanwhile, B was found by comparing with calibrated fiber of the same properties but of length of 0.075 m. The results show an increase in propagation constant (Δβ) and the decrease in beat length (Lb), and show that bending decreases the critical radius of curvature (Rc) related to B. The changes induced on the initial phase of the signal are shown for bending curvatures of radii 0.06, 0.03 and 0.005 m. The linear phase retardation is found to increase more rapidly for bends of R< 0.05 m. The degree of polarization decreases smoothly for bends of R>0.01m. Below this curvature, the fluctuation and great instability in the polarization- state of the output signal are easily detected. All these features are very important in using SMOF in sensitive optical devices especially in long distance fiber communications.